Cardioprotective Activity of Papaya Leaf Ethanol Extract in Isoproterenol-Induced Rats - Jekson Martiar Siahaan; Tiara Larasati; Endy Juli Anto; Binarwan Halim; Syafruddin Ilyas (Jurnal Ners, 2026)
Myocardial infarction is an acute condition caused by impaired blood flow to the heart muscle, causing an imbalance between oxygen supply and myocardial metabolic needs. This study aims to analyze the cardioprotective activity of papaya leaf ethanol extract on isoproterenol-induced Wistar rats. The research method used a laboratory experimental approach with a posttest-only controlled group design with six treatment groups. Papaya leaf extract was prepared at the Medical Phytochemistry Laboratory of UMI, and characterization, phytochemical screening, and CK-MB and LDH levels were conducted at the Integrated Laboratory of the Faculty of Medicine, UMI. Data analysis was performed using ANOVA or Kruskal-Wallis tests, with a significance level of p < 0.05. The results showed a highly significant difference (p < 0.001) in cardiac histopathology scores between the control and treatment groups. Group 2 showed the highest heart damage, while groups 3–6 experienced a decrease in damage scores. Post hoc testing revealed that groups 3, 4, 5, and 6 provided a significant protective effect compared to group 2. CKMB levels increased significantly in group 2, while groups 3–6 showed a significant decrease, particularly in groups 3 and 6. There was no significant difference in LDH levels between groups (p = 0.354), indicating this biomarker is less sensitive in detecting myocardial damage in this model. These results support the potential of papaya leaf ethanol extract as a herbal cardioprotective agent to reduce isoproterenol-induced heart tissue damage.